Orthodontic Treatment in an Endodontically Treated Maxillary Central Incisor: A Case Report - Ramos Reinhard; Mimi Marina Lubis (Dentika: Dental Journal, 2026)
Childhood dental trauma leads to long-term complications that affect pulp health and subsequent orthodontic treatment outcomes. Therefore, this case report concerns a 19-year-old male with protruding maxillary anterior teeth and midline diastema subjected to orthodontic treatment following root canal analysis of the traumatized maxillary central incisor. Orthodontic treatment was initiated after six months of observation. Root length changes were evaluated using the relative root–crown ratio (rRCR) on pre- and post-treatment panoramic radiographs. After 18 months of treatment, significant improvements in tooth consistency, overjet, and overbite were observed. Mild inflammatory root resorption was reported in both teeth due to orthodontic movement, with a greater degree in the important tooth compared to the root canal-treated part. The results showed that orthodontic movement in root canal-treated teeth could be safely performed with controlled force application and appropriate treatment timing. There were no signs of clinical or radiographical ankylosis during treatment, allowing orthodontic tooth movement to proceed without significant complications.